Perlindungan Hukum terhadap Konsumen Pengguna Kosmetik dalam Transaksi E-Commerce Melalui Platform Tiktok - Anna Maria Wijaya; Ferry Irawan Febriansyah; Azis Akbar Ramadhan (Lembaga Teewan Journal Solutions, 2026)
This study is motivated by the high vulnerability of consumers in cosmetic transactions on TikTok Shop due to a mismatch between existing regulations and the impulsive, algorithm-driven nature of social commerce. The research addresses the effectiveness of legal protection, the distribution of responsibility among platforms, sellers, and influencers, and weaknesses in dispute resolution mechanisms. The study aims to critically examine regulatory gaps and propose policy recommendations responsive to digital developments. Using a normative legal research method, the study analyzes legislation on consumer protection, electronic transactions, and cosmetic supervision. Findings reveal three main issues: current regulations do not accommodate content- and algorithm-based transactions; legal responsibilities of platforms and influencers remain unclear, creating accountability gaps; and internal and external dispute resolution mechanisms are ineffective, leading to high underreporting by consumers. The novelty lies in a holistic analysis of responsibility distribution within the social commerce ecosystem and the integration of algorithmic due diligence and a hierarchical Online Dispute Resolution (ODR) model. The study concludes that consumer protection in social commerce requires a hybrid regulatory approach emphasizing compliance-by-design for platforms, clear legal accountability for influencers, and the development of an integrated ODR system with enforceable authority to ensure effective consumer redress.